Determinants of postictal agitation and recovery after tonic‐clonic seizures in generalized and focal epilepsy. Issue 1 (15th February 2022) - Dabir, Aman; Zahoor, Salman; Abou‐Khalil, Bassel W.
Abstract: Objective . The postictal state after bilateral tonic‐clonic seizures is often prolonged and can have significant impact on a patient's quality of life. Considerable variability exists in the magnitude of postictal agitation and in the speed of recovery, the determinants of which are not well understood. We studied postictal behavior after tonic‐clonic seizures in various epilepsy localizations, focusing on postictal agitation and time to responsiveness. Methods . We retrospectively identified 15 adult patients each with idiopathic generalized, left temporal lobe, right temporal lobe and frontal lobe epilepsy. Localization in focal epilepsy was validated by good outcome after resective surgery at one‐year of follow‐up. The first tonic‐clonic seizure with reliable video and EEG for each patient was analyzed by two reviewers, one of whom was blinded to clinical data. Clinical, ictal and postictal variables were collected for each patient and analyzed. Postictal agitation was classified as mild and marked. Results . We reviewed 60 tonic‐clonic seizures, 15 in each of four patient groups. Postictal agitation was observed in 14 patients (23.3%; marked in one and mild in 13). Postictal agitation was most common in patients with left temporal (seven patients) and least common in idiopathic generalized epilepsy (one patient) groups ( p =0.035). Based on subgroup analysis ( n =28), time to responsiveness was 6.6 minutes for frontal, 7.2 minutes for generalized, 10 minutes for right temporal and 15.7 minutes for the left temporal groups ( p <0.05 for frontal vs. left temporal, generalized vs. left temporal). Time to responsiveness was longer in patients with agitation than without (13.9 minutes vs. 7.7 minutes; p =0.048). Patient ictal and postictal characteristics demonstrated no relationship to agitation or latency to postictal recovery. Significance . To mitigate harm, patients must be monitored carefully after tonic‐clonic seizures, especially patients with left temporal lobe epilepsy. Studies evaluating medical and behavioral interventions to promote postictal recovery are needed.